A clinical study on management of hydronephrosis detected antenatally - Khasnis, Ravindra G.; S., Rajshankar (International Journal of Contemporary Pediatrics, 2019)
Background: It is important to detect and manage hydronephrosis early for improved clinical outcomes. The objective of this study is to detect and manage the hydronephrosis which occurs antenatally. Methods: Hospital based cross sectional study was carried out in 20 cases of hydronephrosis in pregnant women as per the inclusion and exclusion criteria laid down for the present study. Patients with mild hydronephrosis were observed. Patients with PUJ obstruction underwent pyeloplasty. Patients with posterior urethral valves underwent cystoscopic dilatation. Patients with VUR were put on prophylactic antibiotic and observed. The patients were followed up post operatively with USG and DTPA scan as indicated. Results: Among the 20 cases with hydronephrosis, majority were males. All cases in terms of side affected were found to be equally distributed. Hydronephrosis was found to be mild in seven (35%) of the cases. Renal dysplasia and bilateral hydronephrosis were found to be the predictors of post natal pathology. Grade 3 and grade 4 were 40% each. There was no persistent case. The most common cause of hydronephrosis was transient hypertension in 5 (33.3%) of the cases. Conclusions: Mild hydronephrosis resolves early and there is no persistence. Renal dysplasia and bilateral hydronephrosis are the important predictors of the post natal hydronephrosis.